Benin : Fifth Review Under the Extended Credit Facility and Request for Extension of the Arrangement. (IMF Staff Country Reports; Country Report ;, 2013)
This paper explains Fifth Review Under the Extended Credit Facility and Request for Extension of the Arrangement report for Benin. The IMF report shows that inflation has returned to normal levels since the petroleum price shock in early 2012 when neighboring Nigeria reduced fuel subsidies, and external imbalances were revised downward. Problems with customs reform, which delayed the 5th fifth review, have been addressed by developing a new approach that takes into account lessons from a suspended previous reform attempt and international best practices.